Mexico : Arrangement Under the Flexible Credit Line and Cancellation of Current Arrangement-Press release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent economic developments, outlook, and risks in the economy of Mexico. The economy continues to grow at a moderate pace. Growth reached 2 1\2 percent in 2015 and is projected to remain at a similar level in 2016. Global financial volatility has increased sharply over the last year, with significant spillovers to Mexico's financial markets. The flexible credit line (FCL) has served the Mexican economy well. The previous FCL arrangements provided valuable insurance in the immediate aftermath of the 2008-09 global financial crisis and during the euro area crisis and the recent turbulent period in the run-up to the start of U.S. monetary policy normalization.